PERBANDINGAN MOTIVASI BERPRESTASI: KARYAWAN TETAP DAN KARYAWAN KONTRAK UKI - Cahyanti, Dwi; Anggraini, Nenny; Hutapea, Ganda T. (Universitas Kristen Indonesia, 2016)
This study aims to determine whether there are differences in the level of achievement motivation among permanent employees with contract employees, in terms of the characteristics of a person who has high achievement motivation, namely: Personal responsibility, needs feedback, keinovatifan, perseverance and difficulties or moderate risk. This study was measured by using a rating scale and type of quantitative research. The study population was employees of the Indonesian Christian University (UKI) and obtained 72 samples each 36 samples of permanent employees, and 36 further samples of employee contracts. Data analysis techniques in this study is an independent test sample t-tests were used to test between two or more variants, using SPSS. This technique uses the basic decision-making if the value of t> t table then no differences were found, however, if t <t table then there is a difference. Further views of signfikansi P> 0.05 then Ho is accepted and vice versa when the value of the significance of P <0.05 then Ho is rejected. The results obtained from the research that there are differences in achievement motivation between permanent employees and contract on a significant aspect of the feedback (2-tailed) 0.038 <0.05, significant keinovatifan (2-tailed) 0.026 <0.05, significant persistence (two-tailed) 0.016 < 0.05, and significant difficulties or moderate risk (2-tailed) 0.026 <0.05. It was therefore concluded there are differences in achievement motivation between permanent employees and contract employees at UKI Cawang.Keywords: Achievement Motivation, Employee Permanent and Contract Employees